Local residents' policy preferences in an energy contested region – The Upper Hunter, Australia. (March 2022) - Colvin, R.M.; Przybyszewski, E.
Abstract: The global momentum toward decarbonisation complicates existing challenges that regional production communities are navigating as they seek prosperous and sustainable futures. In this paper, we explore local residents' priorities for policy processes in the Upper Hunter in New South Wales, Australia. Our research focused on the aim of achieving social wellbeing and economic diversification within this energy-contested region. Using interviews (n = 42), we present several findings that can guide policy processes in the Upper Hunter, and inform processes in other communities. We find that local perspectives on the future of coal are more nuanced than the often binary public debate, indicating a common ground for local policy dialogue. The legacy of conflict between the two dominant sectors – coal mining and thoroughbred breeding – shapes perceptions about new industries for the region. There is an expectation that government will take a leading role in the region's efforts toward economic diversification, though this should be in partnership with industry and community. A plan that provides certainty and diverse, relevant opportunities for the region is desired. From these and other key findings we emphasise the importance of focusing on the social dimensions as a core part of the policy process, and suggest participatory and deliberative processes.